Loading-induced changes on topographical distributions of the zonal properties of osteoarthritic tibial cartilage – A study by magnetic resonance imaging at microscopic resolution. Issue 13 (15th October 2015) - Lee, Ji Hyun; Badar, Farid; Kahn, David; Matyas, John; Qu, Xianggui; Xia, Yang
Abstract The topographical distributions of the zonal properties of articular cartilage over the medial tibia from an experimental osteoarthritis (OA) model were evaluated as a function of external loading by microscopic Magnetic Resonance Imaging (µMRI). T2 relaxation times and cartilage thicknesses were measured at 17.6 µm resolution from 118 specimens, which came from thirteen dogs (six 8-week and seven 12-week after surgery), with and without mechanical loading. In addition, bulk mechanical modulus was measured topographically from each tibia surface. The total thickness decreased significantly under the external loading, in which the relative thickness of the superficial zone (SZ) and the transitional zone (TZ) increased whereas the radial zones (RZs) decreased. In the bulk data, T2(55°) decreased significantly (p<0.001) at all OA-time-points, but T2(0°) decreased without significance (p>0.05) at 8-week. Complex relationships were found in the zonal tissue properties as a function of external loading with the progress of OA. T2 in the superficial zone changed more profoundly than the same properties in the radial zone as a function of external loading at all OA time-points. This study confirms that OA affects the load-induced changes in the molecular distribution and structure of cartilage, which are both depth-dependent and topographically distributed. Such detailed knowledge of mechanobiological changes in specific tibial cartilage zones and locations with OA progress could improve the early detection of the subtle softening of cartilage that accompanies pre-clinical stages of OA.